Guideline-directed medical therapy in real-world heart failure patients with low blood pressure and renal dysfunction - Chen, Xiaojing; Cui, Xiaotong; Thunström, Erik; Pivodic, Aldina; Dahlström, Ulf; Fu, Michael (Clinical research in cardiology, 2021)
Background Among patients with heart failure and reduced ejection fraction (HFrEF), angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers (ACEI/ARB), β-blockers (BB) and mineralocorticoid receptor antagonist (MRA) are known as guideline-directed medical therapy to improve prognosis. However, low blood pressure (BP) and renal dysfunction are often challenges prevent clinical implementation, so we investigated the association of different combinations of GDMT treatments with all-cause mortality in HFrEF population with low BP and renal dysfunction. Methods This study initially included 51, 060 HF patients from the Swedish Heart Failure Registry, and finally 1464 HFrEF patients with low BP (systolic BP ≦ 100 mmHg) and renal dysfunction (estimated glomerular filtration rate (eGFR) ≦ 60 ml/min/1.73m 2 ) were ultimately enrolled. Patients were receiving oral medication for HF at study enrollment, and divided into four groups (group 1–4: ACEI/ARB + BB + MRA, ACEI/ARB + BB, ACEI/ARB + MRA or ACEI/ARB only, and other). The outcome is time to all-cause mortality. Results Among the study patients, 485 (33.1%), 672 (45.9%), 109 (7.4%) and 198 (13.5%) patients were in group 1–4. Patients in group 1 were younger, had highest hemoglobin, and most with EF < 30%. During a median of 1.33 years follow-up, 937 (64%) patients died. After adjustment for age, gender, LVEF, eGFR, hemoglobin when compared with the group 1, the hazard ratio for all-cause mortality in group 2 was 1.04 (0.89–1.21) ( p = 0.62), group 3 1.40 (1.09–1.79) ( p = 0.009), and group 4 1.71 (1.39–2.09) ( p < 0.001). Conclusions In real-world HFrEF patients with low BP and renal dysfunction, full medication of guideline-directed medical therapy is associated with improved survival. The benefit was larger close to the index date and decreased with follow-up time. Graphic abstract